A study of using waste powder rubber in concrete - Sepie, Ahmed Hossameldin (2019)
Now a day’s natural sand is becoming scarcer and costlier due to its non-availability. Waste rubber tire as fine aggregates can be an economical and sustainable alternative to sand. From previews study it shows that tier waste caused certain environmental issue. In this study attempt has been made to utilize waste rubber tire as partial replacement of fine aggregate in the form of powder scrap rubber. Compressive strength, flexural strength, density. (0%, 10% and 5% rubber) have been obtained. It has been shown that flexural strength of rubber powder concrete decreases with the increase of percentage of rubber powder whereas flexural strength of modified concrete is increased with the increase of the percentage of rubber fibers content. The abrasion resistance, carbonation depth, modulus of elasticity and chloride ion penetration of rubber powder concrete and modified concrete were also affected by addition of rubber ash and rubber fibers in concrete. For compressive strength test and flexural test, the concrete is tested on 3, 7, and 28 days. The concrete mixture was designed with water cement ratio of 0.225. For compressive strength test, 18 cubes size 150mm x 150mm x 150mm were tested on 3,7, and 28 days each. Moreover, for flexural test, 12 concrete beam size 500mm x 100mm x 100mm were tested on 7, and 28 days for each test. This study found that the compressive and flexural strength were decrease by increasing tire powder.